A noble channel controller for combined CDMA and SDMA systems - Khatun, Sabira; Mohd Ali, Borhanuddin; Odeh, Nidhal A. S. (2009)
The proposed Channel Controller according to the present invention is an enhancement of the existing CDMA, SDMA or C-SDMA systems by using a limited number of available spreading codes and a novel channel (code, AoA) controller to maintain the maximum orthogonality among users. These channels (codes) are stored in a central pool (BS) and maintained as follows. When a new user requests for a channel, the BS first checks the available channels in terms of codes and Angle of Arrival (AoA); if then are spatially orthogonal to each other, otherwise an available new code will be assigned. If all codes are already utilized then the user will be blocked. This will reduce blocking probability and interference significantly among the users that causes the capacity limit of C-SDMA systems. This dynamic channel controller is able to maximize the channel reuse ratio (maximize the number of users using the same code), thus the total number of served users can be increased significantly, hence the system capacity.